Pendugaan Kriteria Seleksi Genotip Kedelai - Syahrul Zen (Politeknik Negeri Lampung., 2012)
The implementation of the selection that refers to the use of genetic parameter value might expect very effective help in accelerating the discovery of a superior genotypes in accordance with plant breeding program. Twelve promissing lines and check varieties of soybean were planted at KP Sitiung Dharmasraya on two seasons namely MT1 from August-November 2009 and MT2 from December to March 2010. Fertilization with a dose of 75 kg of urea was 125 kg SP36 and 75kg of KCl/ha, the plot size is 2.80 m x 4.0 m. A randomized complete block design with four replication. Variable measured were agronomic characters, yield component and yield. The results the experiment indicated that heritability of all the characters were high (50,43% - 95,98%). Only heritability of plant high at MT1 and yield both environments was medium. The value of guess heritabilitas high on productive branch character per plant and pods per plant is supported by genetic advances and coefficient of average genetic variation is quite high and high, thus both these characters can be reference selection criteria to get productive branches per plant and pods per plant. Keywords: Soybean, genetic variance, heritability, genetic variation coefficient.